Transport survey methods best practice for decision making - Zmud, Johanna (Emerald, 2013)
Every three years, researchers with interest and expertise in transport survey methods meet to improve and influence the conduct of surveys that support transportation planning, policy making, modelling, and monitoring related issues for urban, regional, intercity, and international person, vehicle, and commodity movements. This book compiles the critical thinking on priority topics in contemporary transport policy and planning contexts. The contributed papers cover two key themes related to types of decision-making of importance to the development of data collection on both passenger travel and freight movements: the first theme, Selecting the Right Survey Method, acknowledges the fact that transport survey methods are evolving to meet both changing uses of transport survey data and the challenges of conducting surveys within contemporary society. The second theme, Supporting Transport Planning and Policy, recognizes that the demands on transportation data programs to support decision-making for transport planning and policy making clearly have evolved. The chapters have been selected with particular emphasis on the challenges of the near and medium term future to the design of transport surveys. Rapidly evolving problems and policy contexts are compelling transport researchers to advance the state-of-the-art of methods, tools, strategies and protocols, while assuring the stability and coherence of the very data from which trends can be tracked and understood and on which important decisions can be made.
Includes index.
Keywords: Transportation -- General.; Business & Economics -- Industries -- Transportation.; Transport industries.; Transport planning & policy.; Surveying.; Transportation surveys.; Transportation surveys -- Design.; Transportation -- Planning -- Decision making.; elektronické knihy; electronic books